REMOTE FORM OF EDUCATION, AS ONE OF THE METHODS OF IMPROVING MOTIVATION BY STUDENTS OF DISTANCE LEARNING - Kupnovytska, I. G.; Klymenko, V. I.; Fitkovska, I. P.; Kalugina, S. M.; Belehay, R. I.; Danylyuk, O. I.; Vyvcharenko, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The development of a modern e-learning system promotes the active introduction of distance education. The organization of a mixed form of education at the department of Clinical Pharmacology and Pharmacotherapy involves an education during the session and using the distance contact between faculty and students during the intersessional period. The information technology system of distance learning is provided by personal computers, video and audio equipment. The web-site of the department presents a set of teaching materials, including curriculas, work programs, lecture notes, test assignments, situational tasks, control and individual course work. Distance learning is supplemented with new teaching materials: web lectures, e-learning textbooks and manuals. Lectures are delivered by faculty members in the form of video conferences or webinars. Consultations are conducted in the on-line mode each week at a certain time by the teachers of the department according to the schedule. The website of the department presents methods for implementing practical skills, video stories of individual urgent states on the pathology of internal organs, demonstrates sets of medicines for seven types of first aid kits to improve the students’ knowledge and skills, and to successfully pass the practical part of the state certification of graduates from the discipline "Clinical pharmacy".